STANDARD PRECAUTIONS QUESTIONNAIRE: CULTURAL ADAPTATION AND SEMANTIC VALIDATION FOR HEALTH PROFESSIONALS IN BRAZIL - Fernanda Maria Vieira Pereira-Ávila; Estelle Michinov; Thaís Duarte da Costa Luna; Poliana dos Santos Conde; Natalia Maria Vieira Pereira-Caldeira; Fernanda Garcia Bezerra Góes (Universidade Federal do Paraná, 2019)
Objective: to accomplish the cultural adaptation and semantic validation of the Standard Precautions Questionnaire for Brazilian health professionals.Method: study developed between 2017 and 2018, in Rio de Janeiro. The cultural adaptation included translation, consensus on the Portuguese version, evaluation by experts, back-translation, consensus and comparison with the original version, semantic evaluation and semantic validation. All ethical aspects were respected. Results: for the content validation, the scores ranged from 0.60 to 1.00 and the score was 0.96, indicating that the items are very representative. In the semantic evaluation, 22 (80%) of the items were considered relevant and 24 (100%) of the items were considered clear and understandable by all professionals.Conclusion: the items of the Brazilian version of the instrument were representative, relevant for the clinical practice of health professionals in assessing the obstacles to adhere to standard precautions. Studies are needed to evaluate the psychometric properties of the instrument.